Effects of afforestation on soil microbial diversity and enzyme activity: A meta-analysis - Huang, Hanyue; Tian, Di; Zhou, Luhong; Su, Haojie; Ma, Suhui; Feng, Yuhao; Tang, Zhiyao; Zhu, Jiangling; Ji, Chengjun; Fang, Jingyun (Geoderma, 2022)
•Afforestation enhanced soil fungal diversity and enzyme activity.•Degraded land afforestation increased soil microbial diversity and enzyme activity.•Soil bacterial diversity increased significantly with afforestation duration.•Soil microbial richness changed greater after broad-leaved species afforestation. Afforestation is thought to be one of the key measures for mitigating climate change by capturing atmospheric carbon. However, despite the importance of afforestation in ecosystem functioning, its effects on soil microbial diversity and enzyme activity remain unclear. In this study, we conducted a meta-analysis of these effects, using a newly compiled dataset of soil microbial diversity and enzyme activity before and after afforestation collected from 80 sites worldwide. Soil fungal diversity and soil enzyme activities increased significantly after afforestation, but soil bacterial diversity did not change significantly. Among these soil enzymes, the activities of β-1,4-glucosidase (BG), urease (UREA), alkaline phosphatase (AP), dehydrogenase (DEH), and catalase (CAT) increased by 104.7%, 84.0%, 101.7%, 199.2%, and 58.3%, respectively. The responses of soil microbial diversity and enzyme activities varied across afforestation durations, climate zones, prior land use types, and species. Specifically, soil bacterial diversity and the activity of BG increased significantly with afforestation duration, and the increase in BG activity was higher in tropical than in temperate zones. In degraded sites, both soil microbial diversity and enzyme activities significantly increased after afforestation. In addition, structural equation models showed that soil carbon content, nitrogen content, and soil pH value were significant driving factors for the soil microbial community diversity and soil enzyme activities. Overall, our results provided a comprehensive understanding of the changes in soil microbial diversity and enzyme activity under different afforestation conditions, as well as scientific bases for locally adapted afforestation in the future.